(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Previous reports of the Mexican mealybug, Phenacoccus gossypii Townsend & Cockerell in Japan were confirmed to be misidentifications of the Madeira mealybug, Phenacoccus madeirensis Green. The Madeira mealybug is reported from the Bonin Islands, Kyushu, Shikoku, and the Ryukyu Islands where it is widespread. Distribution of the Madeira mealybug and 25 host records in Japan are given.